2010
DOI: 10.1074/jbc.m110.169284
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Inhibits mTOR Signaling by Promoting the Interaction between mTOR and DEPTOR

Abstract: Resveratrol (RSV) is a naturally occurring polyphenol that has been found to exert antioxidant, anti-inflammatory, and neuroprotective properties. However, how RSV exerts its beneficial health effects remains largely unknown. Here, we show that RSV inhibits insulin-and leucine-stimulated mTOR signaling in C2C12 fibroblasts via a Sirt1-independent mechanism. Treating C2C12 cells with RSV dramatically inhibited insulin-stimulated Akt, S6 kinase, and 4E-BP1 phosphorylation but had little effect on tyrosine phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
131
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(137 citation statements)
references
References 44 publications
4
131
0
2
Order By: Relevance
“…This is corroborated by reports of chemo-preventive effect of resveratrol in various cancer cell lines like, HeLa, A549 and MCF-7 (Cal et al, 2003). Various mechanisms for anti-proliferative action of resveratrol have been proposed including increase in tumor suppressor proteins like, p53, phosphorylation of Rb protein and transcription factors like NF-κB and AP-1 (Liu et al, 2010). Resveratrol is also reported to inhibit PI3K pathway and affects glycolysis to cause cell cycle arrest in B cell lymphomas (Faber et al, 2006).…”
Section: Introductionsupporting
confidence: 62%
“…This is corroborated by reports of chemo-preventive effect of resveratrol in various cancer cell lines like, HeLa, A549 and MCF-7 (Cal et al, 2003). Various mechanisms for anti-proliferative action of resveratrol have been proposed including increase in tumor suppressor proteins like, p53, phosphorylation of Rb protein and transcription factors like NF-κB and AP-1 (Liu et al, 2010). Resveratrol is also reported to inhibit PI3K pathway and affects glycolysis to cause cell cycle arrest in B cell lymphomas (Faber et al, 2006).…”
Section: Introductionsupporting
confidence: 62%
“…Recently, it was shown that inhibition of mTOR activity by resveratrol increased the efficiency of somatic cell reprogramming to form induced pluripotent stem cells (43). Resveratrol is known to cause inhibition of mTOR activity by promoting the association of DEPTOR with mTOR (44). This is consistent with a model where increased DEPTOR inhibition of mTOR facilitates the transition from non-stem cell to pluripotent states.…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, RNAi could not completely inhibit basal AMPK activity. A previous study also did not show the upregulation of phosphorylation level of p70 S6K Thr 389 by RNAi-induced AMPK suppression in C 2 C 12 cells (23). On the contrary, transgenic knockout of AMPK induced myotube hypertrophy and upregulation of p70 S6K phosphorylation by using primary cultured myoblasts under nonstimulated condition (22).…”
Section: Discussionmentioning
confidence: 94%